EL EFECTO DE LOS MIRMECODOMACIOS EN LA TASA DE HERBIVORÍA DE TOCOCA (MELASTOMATACEAE) - Forero Fuentes, Igor Dimitri; Laboratorio de Ecología de Poblaciones, Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
We tested the hypothesis that plants from the genus Tococa {Melastomataceae) which have modified hollow leaves {Myrmecophyles) have lower herbivory damage than plants from another genus (Ossaea) which lack these structures. Our hypothesis is based on the common observation that in ant-plant associations the former protect the latter from herbivore attacks. Our results indicate that there were no significant differences between the herbivory rates ofthe two plant species. Additionally, within Tococa plants there was no significant correlation between the number of ants in the myrmecophyles of agiven plant and the herbivory rate ofthat plan t. We conducted placement experiments in the Tococa plants to observe the behavior ofthe ants. Although the ants were aggressive, wesuggest that they are probably defending their nests rather than the plant itself.